COMPETENCE AND SUITABILITY OF THE SECURITY FUNCTION IN CONTROLLING ENTRY OF COUNTERFEIT PRODUCTS THROUGH THE PORT OF MOMBASA, KENYA - Mwalu, Hudson; Mwaeke, Panuel (Advances in Social Sciences Research Journal, 2020)
This study has been triggered by increase of counterfeit goods in the local markets whose origin is outside Kenya. This study sought to establish the competence and suitability of the security function in controlling entry of counterfeit products through the port of Mombasa. Despite the government putting measures to control entry of counterfeits. The existence of counterfeit goods in the market has led to Kenyans not to get value for money on purchase or end up using goods that might have negative health implications. The government has lost revenue by tax evasion or tax underpayments, money that can be used for infrastructure development in our country. This study examined influence of policy on increased control of counterfeit products at the port of Mombasa and how security personnel employ the policies in controlling entry of counterfeits. This study also assessed the knowledge on counterfeits of security personnel at the port of Mombasa and how this contributes to controlling counterfeiting. This study was anchored on two theories namely two factor theory of motivation and Vroom`s expectancy theory of motivation to describe the behavior of security personnel who are involved in controlling entry of counterfeits. This study utilized descriptive research design and the target population was a total of 248 security personnel drawn from different security agencies who are charged directly with detection and control of counterfeits at the port of Mombasa. This study applied probability sampling design by utilizing stratified random sampling techniques as well as purposive sampling to specifically select a sample size of 106 respondents from the study population. A semi structured questionnaire was the major data collection tools of this study. Gathered data was analyzed quantitatively, aided by the Statistical Package for Social Sciences (SPSS) where averages were computed and findings presented using tables and charts. Findings and recommendations are expected to help reduce or completely curb counterfeits in Kenyan markets as well as provide basis for future research. In all, 57% of the respondent indicated that there was a link between the working conditions and the efficiency of the Security personnel. Working conditions, training, policies and deployment levels influences the efficiency of the security personnel to a level of 90.4 percent. The recommendations from the study are: the government and other relevant agencies should be involved in policy making. The oversight bodies, enforcement agencies and other regulatory agencies should work under one body and involve the National Intelligence and the Directorate of Criminal intelligence for surveillance.